STRUKTUR ORGANISASI RUMAH SAKIT - Nadila Agustina; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
The organisational structure of a hospital is a framework that governs the division of tasks, authority and responsibilities in order to provide effective and efficient healthcare services. This article aims to examine the concepts, functions, and forms of organisational structures implemented in hospitals. The method used is a literature review, involving the collection of various sources related to hospital management. The findings indicate that hospital organisational structures generally consist of top management (the director), medical service units, nursing, medical support, and administrative and financial departments. Each department plays a vital role in supporting the smooth running of operations and improving the quality of healthcare services. Furthermore, a clear organisational structure can enhance coordination, communication, and more effective decision-making. In conclusion, the implementation of an appropriate organisational structure significantly influences a hospital’s performance in delivering high-quality services to the public.